2007
DOI: 10.1016/j.soilbio.2007.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen fertilization reduces diversity and alters community structure of active fungi in boreal ecosystems

Abstract: Nitrogen (N) availability is increasing in many ecosystems due to anthropogenic disturbance. We used a nucleotide analog technique and sequencing of ribosomal RNA genes to test whether N fertilization altered active fungal communities in two boreal ecosystems. In decaying litter from a recently burned spruce forest, Shannon diversity decreased significantly with N fertilization, and taxonomic richness declined from 44 to 33 operational taxonomic units (OTUs). In soils from a mature spruce forest, richness also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
155
7
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(181 citation statements)
references
References 42 publications
16
155
7
3
Order By: Relevance
“…Thus, we hypothesize that had we targeted a less conserved genetic marker than the 18S rDNA gene, we would have observed a stronger correlation between fungal diversity and salinity. Indeed, many studies that detect significant treatment effects on fungal diversity target the more variable ITS region (O'Brien et al, 2005;Allison et al, 2007;Artz et al, 2007). Because diversity estimators such as Chao1 depend on sample size, the absolute number of OTUs estimated would likely increase with further sampling (Colwell and Coddington, 1994;Hughes et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we hypothesize that had we targeted a less conserved genetic marker than the 18S rDNA gene, we would have observed a stronger correlation between fungal diversity and salinity. Indeed, many studies that detect significant treatment effects on fungal diversity target the more variable ITS region (O'Brien et al, 2005;Allison et al, 2007;Artz et al, 2007). Because diversity estimators such as Chao1 depend on sample size, the absolute number of OTUs estimated would likely increase with further sampling (Colwell and Coddington, 1994;Hughes et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Despite their importance for ecosystems, few studies have considered which factors generate and maintain fungal diversity. In general, fungal diversity or composition is thought to be influenced by nitrogen availability (Allison et al, 2007), resource supply (Waldrop et al, 2006), atmospheric CO 2 concentration (Klamer et al, 2002) and soil depth (O'Brien et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism is unknown but both are direct effects of fertilizer itself, and changes in the plant community and litter associated with fertilizers could be involved (Donnison et al 2000;Manning et al 2006). Fungal DNA profiles can also undergo a reduction in diversity in response to fertilizer (Allison et al 2007), but others found that the bacterial communities (but not fungi) can be altered by high rates of fertilizer (Gray et al 2003;Kennedy et al 2004Kennedy et al , 2005.…”
Section: Discussionmentioning
confidence: 99%
“…few studies conducted at individual sites also have shown that elevated N inputs can alter the overall composition of bacterial or fungal communities (17,(19)(20)(21)(22). Understanding of soil microbial community responses to elevated P inputs remains more limited, even though many regions experience elevated inputs of both N and P (2), and anthropogenic activities can alter N:P ratios in soil (1,23).…”
Section: Significancementioning
confidence: 99%